Plasma micronutrients status and gonadotrophin hormone profiles during peripubertal period in female Black Bengal goat - HALDAR, A; PAL, S K; DATTA, M; MAJUMDAR, D; PRAKASH, B S (The Indian Journal of Animal Sciences, 2014)
The aim of the study was to address the micronutrients’ status and hormonal profiles and their relationships during the sexual maturity in Indian prolific Black Bengal goats. Female Black Bengal kids (12) were selected at day 1 of age and subjected to the weekly blood samplings from the day 1 age up to 8 weeks post puberty. Live body weight was recorded weekly. The occurrence of estrus was checked by a teaser buck, followed by transrectal ultrasonographic (USG) examination on 10th day post puberty. Plasma samples harvested from the blood samples were assayed for progesterone to detect luteal function and confirm the timing of puberty onset. The female Black Bengal goats attained puberty at an average age of 25.47±3.84 weeks with a mean body weight of 7.93±0.87 kg. The plasma samples were further utilized for estimating zinc (Zn), iron (Fe), copper (Cu), manganese (Mn), follicle stimulating hormone (FSH) and luteinizing hormone (LH). Plasma Zn, Fe and FSH levels increased during the months preceding puberty onset. Plasma Cu and Mn levels remained higher during the month of puberty. The significant correlations of body weight with plasma FSH, LH, Cu, Zn and Mn levels and between micronutrients and gonadotrophin hormones before puberty onset might have important functions of micronutrients and gonadotrophin hormones for bringing about puberty onset in prolific Black Bengal goats.